Workshop Assistance in PkM’s Proposals and Publication At Institut Agama Islam Hidayatullah Batam - Frangky Silitonga; Tri Muntia Yusri; Karium Jackson M Nainggolan; Widyo Wicaksono; Kintan Sabrina; Heri Nuryanto; Rullyan Syah Lubis; Novelia Abareles (JURNAL KEKER WISATA, 2026)
The Workshop on Assistance in the Preparation of Community Service Proposals (PkM) and the Publication of PkM Journal Articles was held at the Institut Agama Islam Hidayatullah Batam with the aim of increasing the academic capacity of lecturers and students in designing proposals for community service activities and writing scientific articles that can be published in community service journals. This activity was attended by 30 participants consisting of lecturers and students from various study programs. The method of implementing activities is carried out through several stages, namely the delivery of materials, discussions and questions and answers, as well as practice and assistance in the preparation of PkM proposals and the writing of scientific articles. The material presented included the basic concept of community service, the systematics of the preparation of PkM proposals, the method of implementing community service activities, and techniques for writing scientific articles based on community service activities. The results of the activity showed an increase in participants' understanding of the preparation of PkM proposals and the publication of scientific articles. In addition, participants also succeeded in compiling several draft community service proposals as well as draft scientific articles that have the potential to be submitted to the community service grant program or published in community service journals. This workshop activity is expected to encourage an increase in the productivity of lecturers and students in carrying out community service activities and increase the number of scientific publications based on PkM activities